2017
DOI: 10.1038/s41598-017-13987-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological sensitivity of reflexive and nonreflexive outcomes as a correlate of the sensory and affective responses to visceral pain in mice

Abstract: Pain encompasses both sensory and affective dimensions which can be differentially modulated by drugs. Here, we compare the pharmacological sensitivity of the sensory and affective responses using acetic acid-induced abdominal writhings (sensory-reflexive outcome) and acetic acid-induced depression of reward seeking behaviour (RSB, affective-nonreflexive outcome) to a highly palatable food in mice. We found that the expression of RSB critically depends on factors such as sex and previous knowledge and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Discrimination between appetitive and consummatory behaviors in the context of pain-depressed behaviors can also reveal distinct neurobiological underpinnings and pharmacological sensitivity. 25,60 Most studies use sham-operated mice as controls. Indeed, sham operation was undistinguishable from naıve condition as it regards to sensitivity to mechanical von Frey stimulation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrimination between appetitive and consummatory behaviors in the context of pain-depressed behaviors can also reveal distinct neurobiological underpinnings and pharmacological sensitivity. 25,60 Most studies use sham-operated mice as controls. Indeed, sham operation was undistinguishable from naıve condition as it regards to sensitivity to mechanical von Frey stimulation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Reward-Seeking Behavior (RSB) Based on the Approach and Consumption of White Chocolate. The changes in the reward-seeking behavior task when mice were offered palatable food, as previously described, 25 were used to evaluate the affective consequences of neuropathic pain. The task is based on the approach and consumption of white chocolate, which allowed analyzing the appetitive and consummatory aspects of motivational behavior.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…AA induces a writhing response when it is intraperitoneally administered (26,27). It has been reported that the agent may cause the indirect release of noxious substances including bradykinins, serotonin, histamine and PGs (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also tracked research reports that used some of the most recent surrogate pain measures in rodents to investigate different aspects of the pain phenotype, such as interference in physical functioning (postural changes and grip strength deficits), pain-depressed behaviors (exploratory locomotion, home cage activity, borrowing and nesting behaviors, intracranial self-stimulation, and wheel running), and facial expressions in pain conditions. Readers should note here that in addition to these behavioral measures, there are others which are not reviewed here, including (but not limited to) conditioned place aversion and preference induced by pain and analgesia, and specific tests to evaluate depression-like behaviors in rodents; these measures can also yield useful data regarding the rodent pain phenotype (Cobos and Portillo-Salido, 2013;Navratilova et al, 2013;Yalcin et al, 2014;de la Puente et al, 2017). With the measures covered in the present review we aim to provide a sense of how preclinical pain assessment has evolved from earlier decades to the present time.…”
Section: Introductionmentioning
confidence: 99%